2015
DOI: 10.1128/genomea.00166-15
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Lactobacillus acidophilus FSI4, Isolated from Yogurt

Abstract: A new Lactobacillus acidophilus strain, FSI4, isolated from yogurt, was isolated and sequenced in our laboratory. Our data, although supportive of previous conclusions regarding the remarkable stability of L. acidophilus species, indicate accumulating mutations in commercial L. acidophilus strains that warrant further study of the effect of damaged genes on the competitiveness of these bacteria in gut microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Prokaryotic organisms usually have a very well organized single circular chromosome, which minimizes the content of intergenic nucleotide sequences. Generally L. acidophilus strains contain a small number of pseudogenes [ 22 25 ]. The higher number of pseudogenes in L. amylovorus JBD401 suggests that this strain might be in an active stage of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Prokaryotic organisms usually have a very well organized single circular chromosome, which minimizes the content of intergenic nucleotide sequences. Generally L. acidophilus strains contain a small number of pseudogenes [ 22 25 ]. The higher number of pseudogenes in L. amylovorus JBD401 suggests that this strain might be in an active stage of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…LA14, FSI4, ATCC53544, LA1,and DSM20079) from NCBI (Table 1) [21][22][23][24][25][26]. In this study, complete genome sequences of other strains in the NCBI database were used for comparative genome analysis of C5, which were isolated from different hosts, and none were isolated from dogs as in previous studies [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Ramachandran et al [ 11 ] reported that the MLST scheme using seven conserved housekeeping genes ( fusA , gpmA , gyrA , gyrB , lepA , pyrG , and recA ) could be used as an intraspecies subtyping technique for the Lactobacillus complex ( L. acidophilus , L. amylovorus , L. crispatus , L. gallinarum , L. gasseri , and L. johnsonii ); however, two allelic profiles from five L. acidophilus strains were observed only in the gyrA gene. L. acidophilus strains have been considered to have little genome sequence variation [ 20 , 21 , 22 , 23 ], and they are regarded as a monophyletic taxon [ 10 ]. Therefore, higher-resolution strain-level differentiation methods must be developed for L. acidophilus strains.…”
Section: Introductionmentioning
confidence: 99%